The Effect of Different Extraction Solvents on Total Phenolic and Flavonoid Total of Snake Plant (Sansevieria trifasciata var. Laurentii) (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND.The solvent system significantly affects the levels of active substances contained in a plant.OBJECTIVE: This study was conducted to determine the effect of different extraction solvents on the total phenolic content (TPC) and total flavonoid content (TFC) of Sansevieria trifasciata var. Laurentii, which is responsible for the antioxidant activity.DESIGN: The experimental design used in this study was a completely randomized design with various types of solvents as a treatment, using the maceration method. PARTICIPANTS: The treatment consisted of five types of solvents i.e ethanol (96%, 76%, 56%), methanol, and acetone. All treatments were repeatedly for four times to obtain 20 experimental units. The obtained data were analyzed with a variance analysis. If the treatment had a significant effect, it was followed by the Duncan test.KEY RESULTS: The results showed that the various types of solvent treatments had a very significant effect (P<0.01) on total phenolic and total flavonoid levels. The results also showed that methanol solvent had the best treatment which resulted in antioxidant activity of 3.96%, total phenol content of 1124 mg GAE/g, and total flavonoid content of 342.15 mg QE/g based on yield.